PENDIDIKAN GLOBAL SEBAGAI INSTRUMEN BERBANGSA DAN BERNEGARA - Bukman Lian (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Global conception education is an educational process designed to prepare students with intellectual and responsible basic skills to enter a competitive and highly interdependent nation-state life. As a child of the nation both as educators or learners must have a high awareness that life is always related to global issues so that to be able to live a good life we must be able to open up to add insight and knowledge and technology literate so can compete with other countries. Concern for the preservation of the Environment, culture and local wisdom must also be maintained as the foundation of the Indonesian nation and it is not easy to generalize an event and be wiser in